Surface loading of nanoparticles on engineered or natural erythrocytes for prolonged circulation time: strategies and applications - Zhang Si-qi; Fu Qiang; Zhang Yun-jie; Pan Jian-xing; Zhang Ling; Zhang Zhi-rong; Liu Zhen-mi (Acta Pharmacologica Sinica, 2021)
Nano drug-delivery systems (DDS) may significantly improve efficiency and reduce toxicity of loaded drugs, but a few nano-DDS are highly successful in clinical use. Unprotected nanoparticles in blood flow are often quickly cleared, which could limit their circulation time and drug delivery efficiency. Elongating their blood circulation time may improve their delivery efficiency or grant them new therapeutic possibilities. Erythrocytes are abundant endogenous cells in blood and are continuously renewed, with a long life span of 100–120 days. Hence, loading nanoparticles on the surface of erythrocytes to protect the nanoparticles could be highly effective for enhancing their in vivo circulation time. One of the key questions here is how to properly attach nanoparticles on erythrocytes for different purposes and different types of nanoparticles to achieve ideal results. In this review, we describe various methods to attach nanoparticles and drugs to the erythrocyte surface, and discuss the key factors that influence the stability and circulation properties of the erythrocytes-based delivery system in vivo. These data show that using erythrocytes as a host for nanoparticles possesses great potential for further development.